The construction of household livelihood strategies in urban areas: the case of Budiriro, Harare, Zimbabwe - Chevo, Tafadzwa (Rhodes University, Faculty of Humanities, Department of Sociology, 2018)
The main objective of this thesis is to understand and explain the ongoing construction of livelihood activities by urban households in the low-income high-density area of Budiriro, Harare, Zimbabwe in a context characterised by systemic crisis and a general decline of the national economy. The study utilised a mixed methods research approach, which combined both qualitative and quantitative research, including a survey, life histories and focus group discussions. The thesis discusses a diverse range of livelihood activities of Budiriro households, such as formal employment, informal trading and agricultural activities, and the ways in which households seeks to diversify their livelihood portfolio. It does this by way of also examining the contemporary and historical factors influencing the livelihood activities pursued by these households, along with the shocks and disturbances encountered and experienced by households in trying to construct viable livelihoods. The thesis makes useful contributions to the existing literature on livelihoods studies. Firstly, the thesis disaggregates the households by showing the existence of three wealth categories in Budiriro and the varying livelihood strategies of households in different wealth categories. Secondly, the study highlights the significance of intra-household dynamics in Budiriro for livelihoods as well as of inter-household kinship networks, which transcend the urban space and entail multi-spatial livelihoods. Thirdly, the thesis examines livelihoods over time, such that it goes beyond a strictly synchronic examination, therefore providing a diachronic analysis of diverse and complicated livelihood pathways. Finally, the Livelihoods Framework is located within broader macro-sociological theorising including the work of Pierre Bourdieu. In this respect, important insights arise about livelihood choices and practices in the light of ongoing debates within sociology about human agency.
Keywords: Income -- Zimbabwe -- Harare; Cost and standard of living -- Zimbabwe -- Harare; Quality of life -- Zimbabwe -- Harare; Informal sector (Economics) -- Zimbabwe -- Harare; Agricultural wages -- Zimbabwe -- Harare; Households -- Economic aspects -- Zimbabwe -- Harare; Macrosociology; Zimbabwe -- Social conditions -- 1980-; Zimbabwe -- Economic conditions -- 1980-; Livelihoods Framework